2010
DOI: 10.1111/j.1439-0507.2009.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans or Candida dubliniensis?

Abstract: Candida albicans is increasing as an opportunistic pathogen causing candidemia and candidiasis worldwide. In addition, other non-albicans Candida species are now also associated with pertinent infections. These include the closely related C. dubliniensis, which shares many phenotypic similarities with C. albicans. These similarities pose problems in the identification of isolates and have previously led to misidentification of these species. As a result, several identification techniques based on phenotypic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 104 publications
0
28
0
1
Order By: Relevance
“…It has been suggested that C. dubliniensis is more capable of developing antifungal resistance (e.g., to azoles) than C. albicans. 9,12,14 This feature of C. dubliniensis may be associated with its prevalence in AIDS patients, who are often subjected to antifungal treatments. Our results showing the upregulated expression of a number of ergosterol biosynthesis genes in gray cells of C. dubliniensis provide a potential explanation for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that C. dubliniensis is more capable of developing antifungal resistance (e.g., to azoles) than C. albicans. 9,12,14 This feature of C. dubliniensis may be associated with its prevalence in AIDS patients, who are often subjected to antifungal treatments. Our results showing the upregulated expression of a number of ergosterol biosynthesis genes in gray cells of C. dubliniensis provide a potential explanation for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, C. dubliniensis is much less pathogenic and prevalent than C. albicans. 3,11,12 Epidemiological studies indicate that C. dubliniensis is primarily associated with human immunodeficiency virus (HIV)-infected patients. [6][7][8][9] A number of comparative genomic and phenotypic studies of C. albicans and C. dubliniensis have been performed in the previous 2 decades, [12][13][14][15] but what underlying mechanisms or biological characteristics underlying the differences between the 2 species in epidemiology, virulence, and the ability to develop antifungal resistance remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, yeasts were respectively inoculated to Corn Meal Tween-80 Agar (Oxoid Ltd., Basingstoke, UK) and human serum to examine the structures of hyphae and blastoconidia, in addition to the development of germ tubes. All of the isolates having green colonies on CHROMagar Candida medium, developing chlamydospores on Corn Meal Tween-80 Agar, being germ tube positive, and the ability to reproduce at 45°C were considered to be C. albicans [5].…”
Section: Methodsmentioning
confidence: 99%
“…Phenotypic tests are often ambiguous because of yeast strain variability and the high degree of phenotypic switching within a single species (Yang, 2003). Among the non-albicans Candida spp., C. dubliniensis is an increasingly important pathogen (Ells et al, 2011). It is closely related to C. albicans and exhibits similar phenotypic properties (Campanha et al, 2005).…”
Section: Introductionmentioning
confidence: 99%